Pengenalan Etika Moral Kepada Mahasiswa Stikes Santa Elisabeth Medan - Bernad Julvian Zebua; Wetty Mayanora Mendrofa; Ita Monita Munthe; Prilia Handayani Hia (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
The purpose of this research is to find out how knowledge about the moral ethics of Stikes Santa Elisabeth Medan students The study used a cross-sectional design with random sampling and data collection was carried out by distributing online questionnaires via WhatsApp. The population used in this study was a student of the Health Information Management Study Program Level 1, Level 2, and Level 3 with the number of respondents that had been collected totaling 53 respondents and indicators as many as 5 questions. Data collection techniques used questionnaires as primary data, as well as journals and books as secondary data. The results of this study indicate that the introduction of Moral Ethics by Santa Elisabeth Medan Stikes students is classified as good, with 82.2 percent of students agreeing. If you give a questionnaire in the form of a question, the average Stikes Santa Elisabeth Medan student answers it either well or understandably